Methods for Establishing a Renal Cell Carcinoma Tumor Spheroid Model With Immune Infiltration for Immunotherapeutic Studies - Lugand, Leonard; Mestrallet, Guillaume; Laboureur, Rebecca; Dumont, Clement; Bouhidel, Fatiha; Djouadou, Malika; Masson-Lecomte, Alexandra; Desgrandchamps, Francois; Culine, Stephane; Carosella, Edgardo D.; Rouas-Freiss, Nathalie; LeMaoult, Joel (Frontiers in Oncology, 2022)
Tumor spheroids play an increasingly important role in cancer research. Their ability to recapitulate crucial features of tumor biology that are lost in the classically used 2D models along with their relative simplicity and handiness have made them the most studied 3D tumor model. Their application as a theranostic tool or as a means to study tumor-host interaction is now well-established in various cancers. However, their use in the field of Renal Cell Carcinoma (RCC) remains very limited. The aim of this work is to present methods to implement a basic RCC spheroid model. These methods cover the steps from RCC tumor dissociation to spheroid infiltration by immune cells. We present a protocol for RCC dissociation using Liberase TM and introduce a culture medium containing Epithelial Growth Factor and Hydrocortisone allowing for faster growth of RCC primary cells. We show that the liquid overlay technique allows for the formation of spheroids from cell lines and from primary cultures. We present a method using morphological criteria to select a homogeneous spheroid population based on a Fiji macro. We then show that spheroids can be infiltrated by PBMCs after activation with OKT3 or IL15. Finally, we provide an example of application by implementing an immune spheroid killing assay allowing observing increased spheroid destruction after treatment with PD-1 inhibitors. Thus the straightforward methods presented here allow for efficient spheroid formation for a simple RCC 3D model that can be standardized and infused with immune cells to study immunotherapies.